2021
DOI: 10.1080/15427528.2021.1881012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameter estimation and selection in advanced breeding population of white Guinea yam

Abstract: White Guinea yam (Dioscorea rotundata Poir.) is an important tuber crop grown extensively in tropical regions of West African yam belt. Tuber yield, dry matter content, and tolerance to yam mosaic virus are key traits used for identification and selection of superior varieties for commercial deployment. In this study, we estimated genetic parameters for fresh tuber yield, tuber dry matter content, and quantitative field tolerance to yam mosaic virus in 49 clones grown in multi-environment trials (METs). We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
4
8
0
1
Order By: Relevance
“…This is an indication of high selection intensity, which can be imposed on these important traits of the superior genotypes in future yam breeding programmes. High GCV and PCV recorded for tuber yield in this study were in agreement with the findings obtained in the study conducted on advanced breeding population of white yam [37]. Siadjeu et al [38], also reported high GCV and PCV for harvest index which is a yield component trait in a study conducted on D. dumetorum in Cameroon.…”
Section: Genetic Parameters and Broad-sense Heritability Of Assessed ...supporting
confidence: 92%
“…This is an indication of high selection intensity, which can be imposed on these important traits of the superior genotypes in future yam breeding programmes. High GCV and PCV recorded for tuber yield in this study were in agreement with the findings obtained in the study conducted on advanced breeding population of white yam [37]. Siadjeu et al [38], also reported high GCV and PCV for harvest index which is a yield component trait in a study conducted on D. dumetorum in Cameroon.…”
Section: Genetic Parameters and Broad-sense Heritability Of Assessed ...supporting
confidence: 92%
“…Moreover, the pattern of associations among the genetic values of the studied traits suggests that selection based on a multiple-trait selection index has potential for identifying superior breeding lines. Norman et al [ 5 ] also found different associations between white yam genotypes, and studied traits (fresh tuber yields, tuber dry matter content and yam mosaic virus). The genotype by trait association study reveals rich information that can be used by breeders, especially in selection of parents for a breeding programme aimed at improving particular traits [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…is the most cultivated and produced yam species in West Africa with high importance for production [ 4 ]. Despite its importance, several biotic and abiotic factors limit the full potential of the crop as food, feed, industrial application and source of income [ 5 , 6 ]. Biotic and abiotic stress factors contribute to low yields and poor market quality tubers of yams [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
El ñame es una planta dioica del género Dioscorea que contiene alrededor de 600 especies, de las cuales D. rotundata constituye una de las especies de mayor importancia económica alrededor del mundo (Scarcelli et al, 2019).El tubérculo de ñame constituye una de las principales fuentes alimenticias, contiene importantes cantidades de carbohidratos, es fuente moderada de proteína y fibra (Aliyu et al, 2019;Norman et al, 2021), características que hacen de este alimento indispensable para la seguridad alimentaria en los países del continente asiático, americano y africano (Alabi et al,2019;Aighewi et al, 2020).
Respuesta del ñame espino a diferentes densidades de siembra y altura de espalderas: densidades de siembra en Dioscorea rotundataResponse of with yam to different planting densities and trellis height: planting density in Dioscorea rotundata
…”
unclassified